Penerapan Materi Pendidikan Seksual di Sekolah PAUD dalam Upaya Mencegah Kekerasan Seksual - Hayani Wulandari; Fuji Fauzia Lestari (Departement of Mathematics Education, 2023)
The number of sexual violence in early childhood that occurred in Indonesia is based on the Data of the Online Information System for the Protection of Women and Children (SIMFONI-PPA) as of 2023 there were 9,644 cases. Among them were 1,832 cases against men and 8,614 cases against women. The rate of sexual violence in early childhood in Indonesia is still very high, due to a lack of public understanding of sexual education especially for its application to early childhood, the community still feels taboo about discussing sexuality, so that sexual violence occurs a lot, especially among early childhood. Early childhood needs to be given an understanding of their sexual education, so that children can go through their sexuality phase well, the role of parents and educators here is very important in conveying knowledge and understanding about sexual violence in children. This study aims to find out the efforts to prevent sexual violence in early childhood through sexual education material in schools through the song 'I take care of myself'. This research uses a type of qualitative research with a literature review research method or literature study that is carried out by looking for references either through journals, books, theses or websites that are relevant to the problems being faced or researched. According to (Hadna et al., 2016) Creswell, John. W. (2014; 40). The results obtained are by using the media song 'I take care of myself' children can know the boundaries that are allowed and not allowed to be touched by parents or strangers. By providing understanding and also knowledge about sexual violence against children, it can reduce cases of sexual violence in early childhood.